Use and need of removable dental prostheses in an institutionalized Brazilian elderly population: a cross-sectional study - Bruno Luís de Carvalho VIEIRA; Larissa Pereira de MORAIS; Fabiana VARGAS-FERREIRA; Mirna Rodrigues Costa GUIMARÃES; Flávio Freitas MATTOS; Andréa Maria Duarte VARGAS (Sociedade Brasileira de Pesquisa Odontológica, 2021)
Abstract The aim of this study was to assess the use and need of conventional removable prostheses (total and partial) and their associated factors among institutionalized elders. A cross-sectional study was conducted with 1003 elderly people living in non-profit private long-term care institutions in Belo Horizonte, Brazil. Inclusion criteria required a minimum Mini Mental State of Examination (MMSE) score of 21. After the test, 191 individuals were included. Oral examination and interviews were conducted to identify participants' use (throughout the day/every day) and need (do not have/have but do not use) of removable dental prostheses. Socioeconomic health indicators and behaviours were collected from institutional records and via interviews. Bivariate analysis was performed using chi-square test (p<0.05). Poisson regression with robust variance was used in multivariate analysis. Most elders were female (76.4%) and independent in their daily activities (56.5%). Elderly men (PR 1.26) and those whose dental visit was more than one year ago (PR 1.38) showed higher need of dental prostheses. Elderly women (PR 1.68) and individuals with morbidities (PR 1.33) had higher prostheses use. This study demonstrates how socio-demographic characteristics, health indicators, and oral health services impact the use and need of dental prostheses among elders and how these can contribute to public oral health policy development.